Number of ANC Visits at RSIA AMC Metro Based on Mother's Age and Parity - Azza, Azizatul; Nurmalasari, Mieke; Hosizah, Hosizah; Qomarania, Witri Zuama (International Journal of Health and Information System, 2023)
WHO declared COVID-19 as a pandemic on March 11, 2020. Obstacles found in ANC services during the COVID-19 pandemic were pregnant women afraid of contracting COVID-19 if they had to carry out ANC examinations at health services. ANC examinations play an important role in preventing and detecting pregnancy complications. Predisposing factors are one of the factors that influence the behavior of pregnant women in making ANC visits. Some of which are included in the predisposing factors are age and parity. This study aims to determine the effect of age and maternal parity on the number of ANC visits during the COVID-19 pandemic at RSIA AMC Metro. The sample consisted of 100 pregnant women who visited ANC between January and October 2022, and data analysis with multiple logistic regression. The majority of pregnant women were aged 20-35 years (71%), had given birth 2-4 times (36%), and made 1-5 ANC visits (82%). However, the study found that neither age nor maternal parity significantly affected the number of ANC visits during the pandemic at RSIA AMC Metro.